Prophylactic antibiotics for the prevention of cellulitis - Thomas, K.S. (Wounds UK, 2007)
Background: Cellulitis of the lower leg accounts for 2-3% of hospital admissions (Cox et al, 1998), with an average length of in-patient stay of nine days. Studies have reported that up to half of these patients suffer further episodes (Cox et al, 1998; Dupuy et al, 1999). Reducing the recurrence of cellulitis could therefore have a significant impact on both patient morbidity and NHS costs. Aims: To assess whether prophylactic antibiotics prescribed after an episode of cellulitis of the leg results in fewer subsequent attacks and reduced health service costs (PATCH prophylactic antibiotics for the treatment of cellulitis at home). Methods: This article describes two related studies in which participants are randomised to receive either 12 months of prophylaxis (PATCH I) or six months of prophylaxis (PATCH II). The PATCH I study recruits only patients with recurrent disease defined as two or more episodes of cellulitis in the last three years. PATCH II has more open criteria and includes patients with a first episode of cellulitis and also participants with recurrent disease. It is expected that 260 patients will be recruited into PATCH I and 400 patients into PATCH II.